Efektivitas Video Pembelajaran Berbasisi Canva dalam Meningkatkan Hasil Belajar IPS pada Peserta Didik Kelas VII SMP Negeri 5 Pontianak - Gita Lestari, Meilinda; Buwono, Sri; Karolina, Venny; Syahrudin, Husni; Firmansyah, Haris (Indo-MathEdu Intellectuals Journal, 2025)
The aim of this research is to determine the effect of using Canva-based videos on student learning outcomes in Class VII SMP Negeri 5 Pontianak, especially on Social Interaction material. This research uses a quantitative approach with an experimental design involving two groups: a control group (using print media) and an experimental group (using Canva-based video media). The results showed that the Wilcoxon test produced a significant value of 0.445 (greater than 0.05), which indicated there was no significant effect. However, this research also shows that there is a significant impact on learning using Canva-based videos, which can be seen from the paired sample t-test with an asymp sig (2-tailed) significance value of 0.001, which means less than 0.05. This research also shows the importance of using Canva media in learning, with an effect size of 0.518, which shows a moderate influence.